Paradoxes of the EphB1 receptor in malignant brain tumors. Issue 1 (December 2017) - Wei, Wenqiang; Wang, Hongju; Ji, Shaoping
Abstract Eph receptors are a subfamily of receptor tyrosine kinases. Eph receptor-mediated forward and ephrin ligand-mediated reverse signalings are termed bidirectional signaling. Increasing evidence shows that Eph/ephrin signaling regulates cell migration, adhesion, morphological changes, differentiation, proliferation and survival through cell–cell communication. Some recent studies have started to implicate Eph/ephrin signaling in tumorigenesis, metastasis, and angiogenesis. Previous studies have shown that EphB1 receptor and its ephrin ligands are expressed in the central nervous system. EphB1/ephrin signaling plays an important role in the regulation of synapse formation and maturation, migration of neural progenitors, establishment of tissue patterns, and the development of immune organs. Besides, various recent studies have detected the abnormal expression of EphB1 receptor in different brain tumors. However, the underlying molecular mechanisms of EphB1/ephrins signaling in the development of these tumors are not fully understood. This review focuses on EphB1 that has both tumor-suppressing and -promoting roles in some brain tumors. Understanding the intracellular mechanisms of EphB1 in tumorigenesis and metastasis of brain tumors might provide a foundation for the development of EphB1-targeted therapies.